Differential roles of three subclass III C6 transcription factors in the insect-pathogenic lifecycle of Beauveria bassiana - Jian-Ru Feng; Min Li; Sheng-Hua Ying; Ming-Guang Feng (Journal of Invertebrate Pathology, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Unveiling an entirety of TFIIH complex comprising Tfb3, Kin28 and Ccl1, and anti-UV and insecticidal activities of Ccl1 in Beauveria bassiana - Min Li; Jian-Ru Feng; Sheng-Hua Ying; Ming-Guang Feng (Pesticide Biochemistry and Physiology, 2026)

Design optimization of plate anchor for offshore foundation systems - Ru-Ming Feng; Meysam Bayat; Liyun Zhu; Lei Tan (Marine Georesources & Geotechnology, 2026)

Genomics-guided exploration of Nesterenkonia sp. CL21 proteases to produce bioactive peptides with antioxidant and α-amylase inhibitory activities from soy sauce cake hydrolysis - Shieh Feng Chen; Cyn Ru Cheah; Ivan Kai Jie Lim; Hongxuan An; Chun Shiong Chong; Ming Quan Lam; Kah Yaw Ee (Food Bioscience, 2026)

Experimental study on interaction of track and clayey seabed for deep-sea mining vehicles - Bo-Wen Chen; Ru-Ming Feng; Chao Hou; Wei-Qiang Feng (Ocean Engineering, 2026)

Comparative roles of four TFIIH subunits (Tfb1, Tfb2, Tfb4 and Tfb5) in anti-UV and insecticidal processes of Beauveria bassiana - Min Li; Jian-Ru Feng; Sheng-Hua Ying; Ming-Guang Feng (Pesticide Biochemistry and Physiology, 2026)

Regulatory roles of three Zn(II)2Cys6 cluster-coding genes in insect pathogenicity and environmental fitness of Beauveria bassiana - Jian-Ru Feng; Min Li; Sheng-Hua Ying; Ming-Guang Feng (Pesticide Biochemistry and Physiology, 2026)

Spatio-seasonal distribution, precursor transformation, and ecological risks of per- and polyfluoroalkyl substances in port sediments: Insights from a subtropical urban harbor - Chih-Feng Chen; Noralyn G. Dimaongon; Yun-Ru Ju; Chiu-Wen Chen; Yee Cheng Lim; Ming-Huang Wang; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Integrated assessment of trace element enrichment and accumulation in estuarine sediments of southwestern Taiwan using Sr/Ba ratios and pollution indices - Chih-Feng Chen; Noralyn G. Dimaongon; Yee Cheng Lim; Ming-Huang Wang; Yun-Ru Ju; Kent Naiah D. Araña; Chiu-Wen Chen; Cheng-Di Dong (Regional Studies in Marine Science, 2026)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Efficient removal of dissolved tri-n-butyl phosphate from aqueous solution by immobilized bacterial microspheres - Si-Yi Ren; Zhao-Xing Peng; Jin-Ru Feng; Xi-Ming Zeng; Hong-Gang Ni (Journal of Environmental Management, 2025)

Transcriptome-Wide Sequencing Identifies Non-Coding RNAs and Their Competing Endogenous RNA Networks During the Stages of pPGCLCs-Induced Differentiation - Zhan-Zhong Qiao; Qiu-Yuan Pang; Chang Xu; Xin-Lei Feng; Ming-Xin Zang; Ping Wang; Ying Zhang; Yong-Chao Liu; Qian-Ru Han; Wei Shen; Wei Ge; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Microplastic pollution in stony coral skeletons and tissues: A case study of accumulation and interrelationship in South Penghu Marine National Park, Taiwan Strait - Chih-Feng Chen; Yun-Ru Ju; Ming-Huang Wang; Yee Cheng Lim; Chiu-Wen Chen; Yu-Rong Cheng; Cheng-Di Dong (Journal of Hazardous Materials, 2025)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Microplastics in coastal farmed oyster (Crassostrea angulata) shells: Abundance, characteristics, and diversity - Chih-Feng Chen; Yun-Ru Ju; Yee Cheng Lim; Ming-Huang Wang; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Identifying potential toxic organic substances in leachates from tire wear particles and their mechanisms of toxicity to Scenedesmus obliquus - Jie-Ru Jiang; Zhi-Feng Chen; Xiao-Liang Liao; Qian-Yi Liu; Jia-Ming Zhou; Shi-Ping Ou; Zongwei Cai (Journal of Hazardous Materials, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Two new aromatic derivatives from Codonopsis pilosula and their α-glucosidase inhibitory activities - Ru-Yue Wang; Pan-Jie Su; Bing Li; Xiao-Qing Zhan; Feng-Ming Qi; Chun-Wei Lv; Fang-Di Hu; Kun Gao; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Prediction of Metabolic Disorders Using NMR-Based Metabolomics: The Shanghai Changfeng Study - Qi Wu; Qing-xia Huang; Hai-luan Zeng; Shuai Ma; Huan-dong Lin; Ming-feng Xia; Hui-ru Tang; Xin Gao (Phenomics, 2021)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

New phenolic acids from Salvia yunnanensis C.H.Wright - Yun Yu; Yin-ru Wang; Zhen-huan Dong; Wei Li; Shu-Ming Li; Xue-feng Huang (Natural Product Research, 2017)

Quantification of 3D macropore networks in forest soils in Touzhai valley (Yunnan, China) using X-ray computed tomography and image analysis - Jia-ming Zhang; Ze-min Xu; Feng Li; Ru-ji Hou; Zhe Ren (Journal of Mountain Science, 2017)

Cytomolecular characterization and origin of de novo formed maize B chromosome variants - Ya-Ming Cheng; Ying-Ru Feng; Yao-Pin Lin; Shu-Fen Peng (Chromosome Research, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Di-(2-ethylhexyl) phthalate accelerates atherosclerosis in apolipoprotein E-deficient mice - Jin-Feng Zhao; Sheng-Huang Hsiao; Ming-Hua Hsu; Kuan-Chuan Pao; Yu Ru Kou; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Fine structure and primary sensory projections of sensilla located in the labial-palp pit organ of Helicoverpa armigera (Insecta) - Xin-Cheng Zhao; Qing-Bo Tang; Bente G. Berg; Yang Liu; Yan-Ru Wang; Feng-Ming Yan; Gui-Rong Wang (Cell and Tissue Research, 2013)

MpAsr encodes an intrinsically unstructured protein and enhances osmotic tolerance in transgenic Arabidopsis - Jin-Ran Dai; Bing Liu; Dong-Ru Feng; Hai-yan Liu; Yan-ming He; Kang-biao Qi; Hong-Bin Wang; Jin-Fa Wang (Plant Cell Reports, 2011)

Solid-state fermentation of cornmeal with the ascomycete Morchella esculenta for degrading starch and upgrading nutritional value - Gui-Ping Zhang; Feng Zhang; Wen-Ming Ru; Jian-Rong Han (World Journal of Microbiology and Biotechnology, 2010)

A new iridoid glycoside from Scrophularia ningpoensis - Zheng-Rui Niu; Ru-Feng Wang; Ming-Ying Shang; Shao-Qing Cai (Natural Product Research, 2009)

The effect of lanthanide chloride on abscisic acid and electron-transport activity of some crops - Fu Li Zeng; Ming Feng Zhang; Shao Min Zhou; Ji Gui Wu; Ru Wen Deng (Biological Trace Element Research, 1999)